Alternative financing strategies to boost small businesses in Africa - Franck Kuwonu (Africa Renewal, 2017)
A few years ago, more than half a century after the concept was first proposed, the government of Côte d’Ivoire completed construction of the Henri Konan Bédié Bridge, a span over the Ébrié Lagoon linking the north and south of Abidjan, the country’s main city. The project became a reality after the government received development bank and private capital financing.